Outcomes After Infections in Adolescents and Young Adults with Continuous-Flow Left Ventricular Assist Devices. Issue 4 (May 2019) - Chen, Sharon; Cantor, Ryan S.; Auerbach, Scott; Schumacher, Kurt; Almond, Christopher S.; Eghtesady, Pirooz; Alejos, Juan; Das, Bibhuti B.; Hong, Borah J.; Jaquiss, Robert D. B.; Kirklin, James K.; Jeewa, Aamir
Abstract : Infections in adult ventricular assist device patients increase subsequent mortality and stroke risk. Less is known about outcomes after infections in younger patients, where diabetes and obesity, risk factors associated with poor outcomes, are less prevalent. The purpose of this study was to examine outcomes after infections in adolescents and young adults with continuous-flow left ventricular assist devices (VAD) bridged to transplant. From Pediatric Interagency Registry for Mechanically Assisted Circulatory Support and Interagency Registry for Mechanical Circulatory Support registries, we identified patients aged 12–29 years with continuous-flow VADs implanted as bridged to transplant from September 2012 to March 2016. The primary predictor variable was first reported infection. The primary outcome was death on VAD support; secondary outcome was clinical stroke. Kaplan–Meier and Cox proportional hazard methods were used to compare outcomes between patients before or without infection and patients after infection. Ninety-two adolescents (12–18 years of age) and 224 young adults (19–29 years of age) with 3, 748 patient-months of follow-up were included. Adolescents were smaller (body surface area 1.7 vs . 2.0 m 2, p < 0.01) and implanted at higher Interagency Registry for Mechanical Circulatory Support profiles ( p = 0.005); there were no differences in diabetes and obesity, and survival on VAD was similar ( p = 0.22). Among adolescents but not young adults, mortality increased after infection (hazard ratio 8.2, 95% confidence interval 1.6–42.6, p = 0.01). In contrast, stroke risk increased after infection in young adults (hazard ratio 3.1, 95% confidence interval 1.3–7.6, p = 0.01) but not in adolescents. Despite similar underlying risk factors, adolescents have increased mortality after infections, whereas young adults have increased strokes after infections. Both pre- and postimplant factors likely contribute to the discrepancy in outcomes between the two age cohorts. Abstract : Supplemental Digital Content is available in the text.